High platelet distribution width is an independent risk factor of postoperative pneumonia in patients with type A acute aortic dissection - Xie, Xi; Yan, Danyang; Liu, Xin; Wang, Yanjie; Deng, Ying; Yao, Run; Li, Ning (Frontiers in Cardiovascular Medicine, 2022)
Background: Platelet distribution width (PDW), as a widely applied and reliable marker of platelet activation, was associated with adverse outcomes in cardiovascular diseases. However, there is little literature on the relationship between PDW and postoperative pneumonia in patients with type A acute aortic dissection (AAAD). Methods: In this retrospective cohort study, we collected consecutive patients who underwent emergency surgery for AAAD at Xiangya Hospital of Central South University from January 1, 2014 and June 30, 2020. Patients were divided into three tertiles on the basis of the PDW. The independent effect of the PDW on postoperative pneumonia was evaluated using multivariate logistic regression analysis, and smooth curve fitting was performed to visualize the linear relationship between PDW and the risk of postoperative pneumonia in patients with AAAD. Results:A total of 210 patients with AAAD were enrolled and the overall incidence of postoperative pneumonia was 25.24% (n=53). Multivariate logistic regression revealed that PDW was positively associated with the risk of postoperative pneumonia (OR: 1.07, 95% CI: 1.02–1.13, P < 0.05) after adjusting the confounders. Compared with the lowest PDW tertile, the risk of postoperative pneumonia increased by 1.21-fold in the medium PDW tertile (OR: 2.21, 95% CI: 0.73–6.72) and by 3.16-fold in the highest PDW tertile (OR: 4.16, 95% CI: 1.40–12.33). A straight-line relationship was observed between PDW and postoperative pneumonia risk in smoothing spline fitting. Conclusion: Our findings indicate that high PDW is an independent risk factor of postoperative pneumonia in patients with AAAD. Preoperative PDW may serve as an available indicator of pneumonia, which helps identify AAAD patients with a high risk of postoperative pneumonia.